A Review on Autonomous Driving Systems - Salma, Yaakub; Alsibai, Mohammad Hayyan (Penerbit Universiti Malaysia Pahang, 2018)
Autonomous vehiclesareone of the promising solutionsto reduce traffic crashesand improve mobility and traffic system.An autonomous vehicleis preferable because it helps in reducingthe need for redesigning theinfrastructureand becauseit improvesthe vehicle power efficiencyin terms of cost and time taken to reach the destination.Autonomous vehiclescan be dividedinto 3 types:Aerial vehicles, ground vehiclesand underwater vehicles. General, four basic subsystems are integrated to enable a vehicle to move by itself which are: Position identifying and navigation system, surrounding environment situation analysis system, motion planning system and trajectory control system.In this paper, a review on autonomous vehiclesand theirrelatedtechnological applicationsis presentedto highlight the aspects of this industry asa part of industry 4.0 concept.Moreover, the paper discusses the best autonomous driving systems to be applied on ourwheelchair project which aims at convertinga manual wheelchair to a smart electric wheelchair.